An analysis method including orbital overlap directions for predicting π electron properties and reactivity vectors - Xiaofei Shi; Jinshuai Song; Donghui Wei (Nature Communications)
Abstract An analysis method with the name of the Projection of Orbital Coefficient Vector (POCV) has been proposed for predicting π electronic properties, aromaticity, and the directional reactivity of molecules including reactivity vectors. This approach significantly differs from previous computational methods by explicitly accounting for orbital overlap directions. Using the POCV method, accurate predictions of π electron properties and directional reactivity indices have been successfully demonstrated across various unsaturated molecules. To illustrate the advantages of POCV over conventional methods, we present several case studies involving the computation of π electron properties and reactivity vectors for diverse molecular systems, including non-planar axially chiral molecules, nucleophilic and electrophilic carbenes, and linear conjugated molecules. Here we show, the POCV method enables accurate prediction of chemical reaction sites with multiple orbital overlap directions, and facilitates the calculations of π electron properties.